2003
DOI: 10.1089/08977150360517191
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Cerebrovascular Autoregulation Assessment in Traumatic Brain Injury: Validation and Utility

Abstract: A moving correlation index (Mx-CPP) of cerebral perfusion pressure (CPP) and mean middle cerebral artery blood flow velocity (CBFV) allows continuous monitoring of dynamic cerebral autoregulation (CA) in patients with severe traumatic brain injury (TBI). In this study we validated Mx-CPP for TBI, examined its prognostic relevance, and assessed its relationship with arterial blood pressure (ABP), CPP, intracranial pressure (ICP), and CBFV. We tested whether using ABP instead of CPP for Mx calculation (Mx-ABP) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Indeed, the role of ICP in the assessment of dynamic AR remains controversial. However, the three studies comparing dynamic AR determination by CPP or by MABP found significant agreement between both methods (26,36,37). These results support the notion that MABP may reliably replace CPP or ICP for noninvasive assessment of dynamic AR.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the role of ICP in the assessment of dynamic AR remains controversial. However, the three studies comparing dynamic AR determination by CPP or by MABP found significant agreement between both methods (26,36,37). These results support the notion that MABP may reliably replace CPP or ICP for noninvasive assessment of dynamic AR.…”
Section: Discussionmentioning
confidence: 62%
“…' Lang et al (2003) showed that this index is valid if BP is used instead of cerebral perfusion pressure in these patients. This obviates the need for the invasive measurement techniques to determine intracranial pressure.…”
Section: Correlation Indexmentioning
confidence: 97%
“…Intact, partially impaired, or completely disrupted cerebral autoregulation has been reported, and various degrees of impairment have prognostic relevance. 1, 3,13,17,25,32 The pressure reactivity index (PRx), which is an index calculated from a moving correlation coefficient between mean ABP and ICP, has gained wide acceptance in ICU settings, and it has generated a large number of publications.…”
mentioning
confidence: 99%
“…2, 3,14,17,[27][28][29] It is clinically most attractive because it does not require an external stimulus or patient manipulation, and routinely monitored data can be used for clinical research. The PRx has been reported to correlate with outcome after traumatic brain injury (TBI), 14,17 and it is used for online calculation of the optimal cerebral perfusion pressure (CPPopt).…”
mentioning
confidence: 99%
See 1 more Smart Citation